Effect of the Diurnal Variation of the Convective Boundary Layer Height over Metro Manila on Pollutant Concentration - Genelita Tubal; Mariano Estoque; John Holdsworth; Jose Villarin, S.J. (Science Diliman, 2002)
Air pollutants are dispersed throughout a very thin layer of the atmosphere called the boundary layer (BL), and concentrations would be influenced by the thickness of the BL. A monostatic, biaxial, vertically-pointing Mie Scattering 532 nm Nd: YAG lidar was used to observe the development of the daytime BL over Metro Manila in May 1999. The data profiles were background-subtracted, energy-normalized, and range-corrected; 20,000 profiles (30-32 minute period files) were arranged in arrays in time sequential order. A MatLab program with color enhancement capability was developed to display the range-time indicator (RTI) image to visualize the BL.The convective BL height developed with a general pattern; it increased gradually in the early morning, rapidly from mid-morning until noontime, then slowly reaching its maximum height in the early afternoon. (The Maximum height reached by the BL from 1-4 May 1999 was 1635 m). BL height is maintained or lowered very slowly from mid-afternoon until sunset.The BL grew higher when the surface temperature and solar radiation received was greater. Fair-weather active clouds inhibited the growth of the BL. When the relative humidity was higher, the base of the fair-weather cloud field was lower; therefore, the mean BL height was also lower. Prolonged sea breeze modified the convective BL by creating a much lower BL that when there was no sea breeze.Around 75% of the total suspended particulates (TSP) in Metro Manila comes from traffic emissions. Traffic volume over most part of Metro Manila including the main thoroughfares near the lidar site, peaks at around 09:00 Local Standard Time (LST) and between17:00 – 18:00 LST, although traffic volume is lower than at 09:00 LST. The traffic volume reduces to 80% from its morning peak at around noontime. The morning peak of the pollution concentration occurred earlier that that of the traffic. This could be due to the fact that the BL before 09:00 LST was much lower than after it. The pollution concentration on May 1 and 2 was reduced to less than 50% from its morning peak, a reduction much less than expected based on the traffic volume. This could be ascribed to the much higher BL around noontime. The May 2 pollution profile did not have a peak corresponding to the afternoon traffic volume peak because at that time the mean BL height was still very high. The May 3 and 4 pollution profiles were different from the two previous days, with values much greater around noontime. Pollution during those times was concentrated in a much lower layer due to the sea breeze effect.